Global Guidelines in Dermatology Mapping Project (GUIDEMAP): a scoping review of dermatology clinical practice guidelines. (1st October 2021) - Haw, W.Y.; Al‐Janabi, A.; Arents, B.W.M.; Asfour, L.; Exton, L.S.; Grindlay, D.; Khan, S.S.; Manounah, L.; Yen, H.; Chi, C.‐C.; van Zuuren, E.J.; Flohr, C.; et al.
Summary: Background: Clinical practice guidelines (CPGs) play a critical role in standardizing and improving treatment outcomes based on the available evidence. It is unclear how many CPGs are available globally to assist clinicians in the management of patients with skin disease. Objectives: To search for and identify CPGs for dermatological conditions with the highest burden globally. Methods: We adapted a list of 12 dermatological conditions with the highest burden from the Global Burden of Disease (GBD) study 2019. A systematic literature search was done to identify CPGs published between October 2014 to October 2019. The scoping review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) framework. Results: A total of 226 CPGs were included. Melanoma had the greatest representation in the CPGs, followed by dermatitis and psoriasis. Skin cancers had a relatively high CPG representation but with lower GBD disease burden ranking. There was an uneven distribution by geographical region, with resource‐poor settings being under‐represented. The skin disease categories of the CPGs correlated weakly with the GBD disability‐adjusted life‐years metrics. Eighty‐nine CPGs did not have funding disclosures and 34 CPGs were behind a paywall. Conclusions: The global production of dermatology CPGs showed wide variation in geographical representation, article accessibility and reporting of funding. The number of skin disease CPGs were not commensurate with its disease burden. Future work will critically appraise the methodology and quality of dermatology CPGs and lead to the production of an accessible online resource summarizing these findings.